MANAGING MORALE ON THE BATTLEFIELD: A PSYCHOLOGICAL PERSPECTIVE - van ’t Wout, M. C.; van Dyk, G. A. J (Scientia Militaria - South African Journal of Military Studies, 2015)
From historical writings to current day, morale has always been regarded as a major determinant of success on the battlefield. The management of morale is thus also important in the South African National Defence Force (SANDF) for ensuring combat readiness. Numerous studies have been done in the past in various countries to investigate the factors influencing morale. A summary of the factors identified in the literature was used in the study on which this article is based, to compile a psychological plan to manage morale on the battlefield. Some recommendations for possible actions toward improving morale are included.